High-efficient and Friendly Energy Utilization of Rail Electric Traction - FENG Jiang-hua; ZHANG Zhi-xue (机车电传动)
According to the several important segments of rail-traffic power transmission and conversion in rail electric traction driving system, DC & AC traction supply system and etc, development trend of energy saving and technic measures to improve energy usage were introduced, which provided thoughts to raise electric energy utilization ratio of the whole rail electric traction traffic field.